2020
DOI: 10.7554/elife.55832
|View full text |Cite
|
Sign up to set email alerts
|

Temporal integration of auxin information for the regulation of patterning

Abstract: Positional information is essential for coordinating the development of multicellular organisms. In plants, positional information provided by the hormone auxin regulates rhythmic organ production at the shoot apex, but the spatio-temporal dynamics of auxin gradients is unknown. We used quantitative imaging to demonstrate that auxin carries high-definition graded information not only in space but also in time. We show that, during organogenesis, temporal patterns of auxin arise from rhythmic centrifugal waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 70 publications
6
90
0
Order By: Relevance
“… 49 , movie S07). More recently, Galvan-Ampudia et al ( 50 ) observed radially traveling auxin maxima in the shoot apical meristem of Arabidopsis . Our results extend their finding to the lateral displacement of maxima in gerbera heads.…”
Section: Discussionmentioning
confidence: 99%
“… 49 , movie S07). More recently, Galvan-Ampudia et al ( 50 ) observed radially traveling auxin maxima in the shoot apical meristem of Arabidopsis . Our results extend their finding to the lateral displacement of maxima in gerbera heads.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the embryos/seeds reach maturity in a more or less synchronized manner. This difference in the zero-to-one effects of auxin in the differentiation of megaspores, microspores and guard cells in comparison to the dose-dependent delay in embryos in the rgtb1 / rgtb1 plants may be explained by the multicellularity of the embryos [ 67 , 68 , 69 ]. In all the described structures, the increased concentration of auxin in the (sporophytic) tissues surrounding the cell/embryo seems to be inhibitory for realization of a correct developmental plan [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this scheme, the inhibitory effect of the existing primordia on the vicinal formation of a new primordium is correspondent to the auxin depletion by drainage into the existing auxin convergence from its vicinity (Mirabet et al, 2012). On the other hand, leaf primordia and young leaves are known to be major sources of auxin in the shoot apex (Cheng et al, 2007; Galvan-Ampudia, C.S. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%